Breaking the Barriers of Farm Income through Supplementary Enterprises: A Step beyond Farming Systems - Chandre Gowda, M. J.; H A Bindu,; G. Sai Tejashree , (Indian Journal of Extension Education, 2025)
The study was conducted in ten districts of Karnataka in which Krishi Vigyan Kendras(KVKs) have introduced improved agricultural technologies and practices in selected villages during 2022. The interventions aimed at enabling the farmers to realize higher income from farm and non-farm activities.  Propensity Score Matching was used to overcome the bias in sampling of treated and control category households. The probit analysis was applied to study the factors influencing household income. Agriculture + Horticulture + Livestock and Agriculture + Livestock were the most practiced farming systems by treatment and control group farmers, respectively. Increase in average net income was noticed in both the categories of the farmers over the benchmark. However, the highest net income was achieved by the treatment group farmers practicing Agriculture + Horticulture + Livestock + Supplementary enterprises.The importance of technological interventions was particularly evident when the same combination of enterprises practiced by the control category could only fetch lesser income.